New phorbol ester derivatives as potent anti-HIV agents. (15th October 2021) - Li, Qi-Run; Cheng, Yung-Yi; Zhao, Lei; Huang, Xiao-Lei; Jiang, Xiao-Gang; Cui, Ya-Dong; Morris-Natschke, Susan L.; Goto, Masuo; Chen, Chin-Ho; Lee, Kuo-Hsiung; Chen, Dao-Feng; Zhang, Jian
Graphical abstract: Abstract: Tigliane esters show many biological activities, including anti-HIV-1 activity. Our aim in this study was to establish structure-anti-HIV activity relationships for four series of tigliane-type diterpenoids. We synthesized and evaluated 29 new phorbol ester derivatives for anti-HIV activity and for cytotoxicity against human tumor cell lines. Among them, three derivatives, two phorbol-13-monoesters (5d and 5e ) and a phorbol-12, 13-diester (6a ), showed significant anti-HIV activity. We found that better anti-HIV activity was often associated with a shorter acyl ester at C-13. Particularly, compounds with a phenyl ring in the ester side chain exhibited excellent anti-HIV activity and had good safety indexes. Due to its significant anti-HIV potency with a high selectivity index, phorbol-12, 13-dicinnamoate (6a ) was chosen as the potential candidate for further preclinical trials.